Utilization Of Plasticizers And Lubricants Derived From Palm Oil On Rheological And Mechanical Properties Of Styrene Butadiene Rubber - Lim, Chow Peei (Universiti Sains Malaysia, 2022)
Research is increasingly focused on natural lubricants and plasticizers due to the high concentration of polycyclic aromatic hydrocarbon in processing oil, which is harmful to human health. This research focus on utilization of lubricants and plasticizers derived from palm oil on the rheological, mechanical properties and thermal aging of styrene-butadiene rubber (SBR) compounds. These lubricant and plasticizer known as Glycerol Trioleate (GTO), N-Butyl Stearate (NBS), Ethylene Bis-Steramide (EBS) Ethylene Bis-Oleamide (EBO), Pentaerythritol Tetrastearate (PETS) and Stearyl Stearate. The abrasion resistance, appearance (visual), and cure characteristics of these lubricants and plasticizers on SBR were examined and compared with other mineral lubricants and plasticizers. The SBR compounds (GTO, EBS and stearic acid) which exhibited better abrasion resistance and cure properties equivalent to processing oil-based SBR compound were selected for further investigation on the mechanical properties and aging behaviour. Tensile properties results have demonstrated the SBR compounds with EBS and combination of EBS with GTO shows similar mechanical properties than SBR compounded with processing oil. This is because lubricant and plasticizer derived from palm oil able to promote the carbon black dispersion in the SBR compound. The results of thermal ageing demonstrate that all SBR compounds have been adversely affected. However, the tensile properties of SBR compounds with natural lubricants and plasticizers show characteristics of aged samples that are similar to those of SBR compound with processing oils. This indicates that the use of lubricants and plasticizers derived from palm oil would not adversely affect the tensile properties after ageing. Based on the findings, EBS and EBS with GTO are suitable substitutes as processing aids for petroleum-based processing oils in SBR compounds.